Multicentric and Observational Study of Omalizumab for Chronic Spontaneous Urticaria in Real-Life in Colombia (2022)
ABSTRACT: Although chronic urticaria (CU) is a common, cause of medical consulting both in general practitioners and allergist specialists worldwide, there is little information about its behavior and management in Latin America. Currently, national and international guidelines recommend using Omalizumab for cases refractory to management with antihistamines. Despite advances in the knowledge of Omalizumab for the management of CU, although there are few studies in underdeveloped countries, there are many studies evaluating the impact of Omalizumab treatment. There is not clinical information related with CSU-Omalizumab in patient settled in the Caribbean area. This research aims to evaluate the management of CU with Omalizumab in a real-life scenario in Colombia.